DESIGNING A MATHEMATICS CURRICULUM - Lee Peng Yee (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2010)
A decade of PMRI saw the changes in the classroom in some of the primaryschools in Indonesia. Based on observation, we can say that though themathematics syllabus in Indonesia did not change, its curriculum has changedunder the movement of PMRI. Â In this article, we put in writing some of theexperience gained through the involvement in designing curricula since 1971.Hopefully, some of the observations made may be of use to the colleagues inIndonesia. The discussion below will cover some deciding factors in designing acurriculum, some practices, and the latest trends. For convenience, we keep thediscussion general, and do not refer to a specific syllabus. Also, in many cases,we refer mainly to secondary schools, that is, Grade 7 to Grade 10.